KAJIAN AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN TEMBELEKAN (Lantana camara L) BERDASARKAN TINGKAT KEPOLARAN PELARUT - Oktavian Mangela; Ahmad Ridhay; Musafira Musafira (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2016)
The investigation about the antioxidant activity of tembelekan (Lantana camara L) leaf extract based on level polar solvent . Has been done the aim of this study was to determine the IC50 value and to know the content of antioxidant compounds from tembelekan leaf extract based on the level of polar solvent the extraction of tembelekan leaf was done with maceration method . The result showed that ethyl acetate extract of tembelekan leaf has the highest antioxidant activity with IC50 value was 71,70 ppm. Keywords: Tembelekan ( Lantana Camara L ) , IC50 , Antioxidant , DPPH